Cardiopulmonary Fitness among Nursing Students of Mid-Western Nepal: A Descriptive Cross-Sectional Study - Pun, Dilli Bahadur; Thapa, Bobby (Medical Journal of Eastern Nepal, 2022)
Background Cardiopulmonary fitness in terms of maximum aerobic capacity (VO2 max) reflects the total physical fitness of a person. Nursing students, who are the future health care workers and a role model, are more likely to encourage their patients to adopt healthy habits. However, there is a gap of evidence about nursing student’s physical fitness. Thus, this study aimed to assess the cardiopulmonary fitness in terms of VO2 max among the nursing students of Nepalgunj Nursing campus, Banke, Nepal. Methods A cross sectional study was conducted to assess the cardiopulmonary fitness among the nursing students enrolled in Nepalgunj Nursing Campus using a non-probability purposive sampling technique. Queen’s College Step test was conducted along with anthropometric measurements. Descriptive analysis, and chi square test was done using SPSS v20. Ethical approval was taken from the Institutional Review Committee, Institute of Medicine, Tribhuvan University (Ref-99(6-11) 077/078). Results Total 189 female nursing students participated whose mean age was 21.06±3.41 years. Thirty-six (19%) were overweight and 11 (5.8%) were obese. Out of total, 56 (29.6%) had a high-risk waist hip ratio. Almost half (42.9%) of the respondents had superior level of VO2 max with mean VO2 max value of 43.605±10.686. There was a significant association between VO2 max and BMI (X2 =18.856, p=0.016). Conclusion There is superior level of cardiopulmonary fitness among the young nursing adults. Since BMI is associated with VO2 max, one should be aware of maintaining a normal BMI.